Growth and productivity of selected fodder grasses intercropped under mature coconut and rubber plantations at Vellanikkara, Thrissur - Jose, R.M.; Jamaludheen, V.; Kunhamu, T.K.; Santhoshkumar, A.V.; Raj, A.K. (Indian Journal of Agroforestry, 2019)
A field experiment was conducted at Vellanikkara, Thrissur, Kerala to assess understory productivity of four fodder grasses viz., Brachiaria ruziziensis (congo signal), Panicum maximum (guinea), hybrid napier cultivar CO-3 and CO-5under mature coconut (Cocos nucifera) and rubber (Hevea brasiliensis) plantations, which are the two prominent land-use systems in Kerala, from May 2017 to February 2018. The selected fodder grasses were planted in beds (10 m × 1 m × 0.3 m) in the understory of mature coconut and rubber plantations. Coconut grown fodder grasses showed maximum plant height with a per cent increase of 3.73, 8.97 and 5.28%, respectively over control for first three harvests. Tiller production also varied significantly. At fourth harvest, with maximum number of tillers clump-1, the coconut grown fodder grasses exhibited only 36.35% decrease in tillers whereas it was 78.29% in rubber as compared with open. The mean number of leaves clump-1 observed in open grown fodder grasses was 127.25, whereas it was only 66.71 and 16.04 in coconut and rubber plots, respectively at the second harvest, which recorded the maximum leaf production. Understory photosynthetically active radiation (PAR) transmittance ranged from 39.84-56.08% in rubber and coconut, respectively. Coconut grown fodder grasses showed an equally good performance in growth and yield attributes with the open whereas a substantial reduction in the yield was observed in fodder grasses grown in the understory of rubber.